HEALTH INSURANCE LEGAL COUNSELING MIGRANT WORKERS IN PONOROGO - Arief Budiono; Absori Absori; Rika Maya; Syaifuddin Zuhdi; Moh Indra Bangsawan; Wafda Vivid Izziyana (LPPM Universitas Bina Bangsa, 2022)
Article 28 H paragraph (1) of the 1945 Constitution directly states that social security is the right of every human being. Article 34 paragraph (1) again mentions the constitutional basis for the need for a social security system. The next constitutional basis is Law Number 40 of 2004 concerning the National Social Security System. This background means that the state has a duty to build a comprehensive social security system and provide a wider sense of